2016
DOI: 10.51406/jagse.v15i1.1468
|View full text |Cite
|
Sign up to set email alerts
|

Economic Analysis of Suya Production in Benin City, Edo State, Nigeria

Abstract: The study focused on economic analysis of suya production in Benin City, Edo State of Nigeria. Its specific objectives were to examine the socio-economic characteristics of suya producers, estimate the costs and returns of suya production, examine the relationship between gross income of suya production and the inputs affecting it, and identify the constraints limiting suya production. A total of 33 suya producers identified in the study area using snowballing sampling technique were used for the study. A stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
0
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
3
0
0
Order By: Relevance
“…This is because culturally women in the study area are not directly involved in the business of suya. This finding agrees with Iliyasu et al (2008) and Ahmadu and Aduwa (2015). The survey revealed that 36% of the suya agribusiness entrepreneurs had primary level education; 50% had secondary education.…”
Section: Results and Discussion Socio-economic Characteristics Of Suy...supporting
confidence: 92%
See 2 more Smart Citations
“…This is because culturally women in the study area are not directly involved in the business of suya. This finding agrees with Iliyasu et al (2008) and Ahmadu and Aduwa (2015). The survey revealed that 36% of the suya agribusiness entrepreneurs had primary level education; 50% had secondary education.…”
Section: Results and Discussion Socio-economic Characteristics Of Suy...supporting
confidence: 92%
“…Total costs for suya agribusiness have to rise by 223% before the agribusiness efficiency ratio would be down to 1, which is the break-even point. These findings agree with that of the earlier mentioned studies (Iliyasu et al, 2008;and Ahmadu and Aduwa 2015) that suya agribusiness is profitable.…”
Section: Efficiency Of Suya Agribusiness Enterprises In the Study Areasupporting
confidence: 94%
See 1 more Smart Citation
“…One of the important parameters for the investment criterion in the egg sector is the return on investment. Ahmadu et al (2019) have found that the return period of investment in Nigeria is on average three years. The return period of investment for organic egg production systems in Turkey was detected to be 2.3 years by ORAN, (2015).…”
Section: Analysis Of Different Production Systems In Laying Hen Enter...mentioning
confidence: 99%